Novel p-n heterojunction photocatalyst fabricated by flower-like BiVO4 and Ag2S nanoparticles: Simple synthesis and excellent photocatalytic performance - Wei, Zhao; Xinyue, Tu; Xiaomeng, Wang; Benlin, Dai; Lili, Zhang; Jiming, Xu; Yue, Feng; Ni, Sheng; Fengxia, Zhu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •The degradation efficiency of TC over the 0.3-p-Ag2S/n-BiVO4 can be achieved 90.2%.•Ten intermediate products for TC degradation were verified by the GC-MS.•The enhancing photocatalysis mechanism was attributed to the facilitated charge transfer. Three-dimensional microsphere p-Ag2S/n-BiVO4 p-n heterojunction photocatalyst was successfully fabricated via depositing p-type Ag2S on n-type BiVO4, which showed excellent photocatalytic performance, compared with BiVO4 and Ag2S, for the photocatalytic degradation of tetracycline under visible light irradiation. The enhancing photocatalytic performance can be attributed to the facilitated charge transfer, and the increased lifetime of the charge carriers confirmed by the results of time-resolved fluorescence spectra and photoelectrochemical measures. Moreover, 10 photocatalytic degradation intermediates and products were also identified by the gas chromatography-mass spectrometer. Finally, the photocatalytic enhancement mechanism over p-Ag2S/n-BiVO4 was discussed. The strategy to form three-dimensional microspheres p-n heterojunction photocatalyst may open a new opportunity to design highly efficient photocatalyst for environmental treatment to control pollution.